2021
DOI: 10.1002/ppul.25405
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of bronchoalveolar lavage in children with complicated intrathoracic tuberculosis

Abstract: Introduction: Bronchoscopy can be a useful tool in children with pulmonary tuberculosis (PTB) with severe disease potentially requiring intervention or in the face of diagnostic dilemmas. The aim of this study was to determine the value of Xpert MTB/RIF assay (Xpert) on bronchoalveolar lavage (BAL) samples in children with complicated PTB. Methods: Retrospective analysis of children with clinically diagnosed PTB, who underwent routine bronchoscopy over a 5-year period at a large referral hospital. BAL and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…An interim joint analysis of these two studies has shown similar sensitivity between the three methods, but lower sensitivity than the microbiological reference standard, and high specificity with less than 10% of combined invalid and error results [64]. Finally, bronchoalveolar lavage (BAL), which consists in aspirating normal saline instilled in a subsegment of the lung through flexible bronchoscopy, has a diagnostic performance equivalent to GA in children with presumptive TB, with no or little added value when both techniques are done [23]. It has a place in children with severe intrathoracic TB who cannot be confirmed on less invasive specimens.…”
Section: Microbiological Sample Collection Methods and Diagnostic Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…An interim joint analysis of these two studies has shown similar sensitivity between the three methods, but lower sensitivity than the microbiological reference standard, and high specificity with less than 10% of combined invalid and error results [64]. Finally, bronchoalveolar lavage (BAL), which consists in aspirating normal saline instilled in a subsegment of the lung through flexible bronchoscopy, has a diagnostic performance equivalent to GA in children with presumptive TB, with no or little added value when both techniques are done [23]. It has a place in children with severe intrathoracic TB who cannot be confirmed on less invasive specimens.…”
Section: Microbiological Sample Collection Methods and Diagnostic Yieldmentioning
confidence: 99%
“…The automated Mycobacterial Growth Indicator Tube (Bactec MGIT, Becton Dickinson Microbiology Systems, Cockeysville, MD, USA), has higher sensitivity, a shorter time to results, and improved reproducibility compared to culture on solid media such as Löwenstein-Jensen (LJ) [19]. Culture yield is usually low (30% to 40%) in children with intrathoracic TB, although certain disease manifestations are associated with much higher diagnostic yields [11,[20][21][22][23]. Classical decontamination methods used on samples prior to culture are known to kill up to 30% of the MTBc population and may be too harsh for paediatric paucibacillary specimens and result in a loss of viable organisms for culture [24].…”
Section: Mycobacterial Culture and Identificationmentioning
confidence: 99%
“…Overall, bacteriological confirmation was achieved in 78.7% from all samples. 23 Bronchoscopy is unlikely to be; indeed, should not be, the first investigation used to identify the organism. This is especially true in the developing world, which is impacted by limited resources.…”
Section: Broncho-alveolar Lavagementioning
confidence: 99%
“…The median duration of treatment was significantly different for children with a positive culture compared with those with a negative culture (7 versus 14.5 days, p < 0.001); in contrast, there was no difference among children with a positive versus a negative Xpert (11 versus 8 days, p = 0.36). 23…”
Section: Bronchoscopic Diagnostic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation